2023
DOI: 10.1002/anie.202310162
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Growth of Macroscopically Structured Supramolecular Hydrogels through Orchestrated Reaction‐Diffusion

Hucheng Wang,
Xiaoming Fu,
Guanyao Gu
et al.

Abstract: Living organisms are capable of dynamically changing their structures for adaptive functions through sophisticated reaction‐diffusion process. Here we show how active supramolecular hydrogels with programmable lifetime and macroscopic structures can be created relying on a simple reaction‐diffusion strategy. Two hydrogel precursors (poly(acrylic acid) PAA/CaCl2 and Na2CO3) diffuse from different locations and generate amorphous calcium carbonate (ACC) nanoparticles at the diffusional fronts, leading to formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Remarkably, the S 2 hydrogel underwent almost complete degradation within 8 h at RT (Figure a). The degradation can be attributed to the disruption of electrostatic interactions between polymer chains, achieved through the inhibiting effect of Na + and Cl – ions (Figure b). Furthermore, the longer degradation time (within 48 h) of S 2 hydrogel observed in PBS (1×) (Figure S8) could be attributed to the solubilities of polymers in different electrolytes according to the “Hofmeister series” .…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, the S 2 hydrogel underwent almost complete degradation within 8 h at RT (Figure a). The degradation can be attributed to the disruption of electrostatic interactions between polymer chains, achieved through the inhibiting effect of Na + and Cl – ions (Figure b). Furthermore, the longer degradation time (within 48 h) of S 2 hydrogel observed in PBS (1×) (Figure S8) could be attributed to the solubilities of polymers in different electrolytes according to the “Hofmeister series” .…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have explored patterning multicomponent gels by acid diffusion, demonstrating it is a powerful approach to generating dynamic multidomain gels with evolving and/or transient spatially resolved characteristics. Although studies in which H + diffusion is used to trigger gelation are increasingly common, very few studies have investigated the diffusion of other active species in order to trigger gel formation. ,, Having demonstrated that CaCl 2 was an effective alternative trigger for multicomponent systems, yielding fully characterized self-sorted multicomponent gels across all length scales, we next decided to explore whether calcium ions could be used as a mild, diffusible trigger to pattern these multicomponent gels. The goal was to achieve spatial and temporal control of Nap-FF assembly by diffusing CaCl 2 within a preformed DBS-CONHNH 2 matrix.…”
Section: Results and Discussionmentioning
confidence: 99%